Listeria Monocytogenes - Alfred Nyila, Monde (IntechOpen, 2018)
The book "Listeria monocytogenes" describes different topics that deal with L. monocytogenes in medical research, modelling the behaviour of the organism in meat, quality assurance of raw food material and food products, the impact of environmental stresses in virulence traits of L. monocytogenes relevant to food safety, contamination, prevention and control in food processing and food service environments. The aim of this book is to introduce the reader to different approaches, methods, and tools in understanding the pathogen, Listeria monocytogens, with regard to primary and public health, food safety, pathogenicity, virulence, and its ubiquity. Topics covered in this book deal with L. monocytogenes in medical research. modelling the behaviour of the organism in meat, quality assurance of raw food material and food products, the impact of environmental stresses in virulence traits of L. monocytogenes relevant to food safety, contamination, prevention and control in food processing and food services environments.